2018
DOI: 10.1039/c8nj03196g
|View full text |Cite
|
Sign up to set email alerts
|

Unveiling point defects in titania mesocrystals: a combined EPR and XPS study

Abstract: Titania mesocrystals, prepared using a polyethylene template, were studied by a combination of electron microscopy, XPS and EPR techniques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…Mesocrystals are a quite new and fascinating nanostructure, which is composed of aligned nanocrystals [204][205][206]. The mesocrystal structure might be synthesized from the primary nanocrystals by self-assembly-based crystallization (non-classical crystallization, as shown in Figure 16 [204]) and a template method (e.g., polyethylene template [207]). For example, Wu et al confirmed that rutile titania mesocrystals have been formed by the rapid crystallization by particle attachment (CPA), i.e., non-classical crystallization [208].…”
Section: Titania Mesocrystalsmentioning
confidence: 99%
“…Mesocrystals are a quite new and fascinating nanostructure, which is composed of aligned nanocrystals [204][205][206]. The mesocrystal structure might be synthesized from the primary nanocrystals by self-assembly-based crystallization (non-classical crystallization, as shown in Figure 16 [204]) and a template method (e.g., polyethylene template [207]). For example, Wu et al confirmed that rutile titania mesocrystals have been formed by the rapid crystallization by particle attachment (CPA), i.e., non-classical crystallization [208].…”
Section: Titania Mesocrystalsmentioning
confidence: 99%
“…51,53 However, the Ti was found in 4+ oxidation state in Ce 0.5 Ti 0.5 -UiO-66-NH 2 as observed from the Ti2p 3/2 , 2p 1/2 , and the satellite peak positions at binding energies of 458.31, 463.99, and 470.10 eV, respectively, in Figure 3c. 54,55 After calcination, the core-level spectra of Ce3d of CeO 2 and the phase-pure Ce 0.75 Ti 0.25 O 2 in Figure 3d,e exhibited as many as 10 peaks, wherein five doublets correspond to 3d 5/2 (assigned as x) and 3d 3/2 (assigned as y). The peaks labeled as x − y (886.3 and 902.4 eV), x″ − y″ (892.6 and 910.8 eV), and x‴ − y‴ (898.3 and 916.8 eV) are assigned to primary photoionization of Ce 4+ arising from Ce 3d 9 4f 2 O2p 4 , Ce 3d 9 4f 1 O2p 5 , and Ce 3d 9 4f 0 O2p 6 final states, respectively.…”
Section: Characterization Resultsmentioning
confidence: 99%
“…Meanwhile, NiS occupying the S defect results in the shift of binding energy. 42,43 The binding energy of Cd in 17%-NiS/ Cd 0.5 Zn 0.5 S was changed, indicating the formation of the heterojunction between NiS and Cd 0.5 Zn 0.5 S. In the Zn 2p spectrum (Fig. 3c), two peaks at 1021.2 eV (Zn 2p 3/2 ) and 1044.3 eV (Zn 2p 1/2 ) are assigned to the Zn (+2) chemical state of Cd 0.5 Zn 0.5 S. 44 The Ni 2p spectra of NiS and 17%-NiS/Cd 0.5 Zn 0.5 S are shown in Fig.…”
Section: Resultsmentioning
confidence: 99%